2019
DOI: 10.3390/ijerph16091525
|View full text |Cite
|
Sign up to set email alerts
|

The Health Risks of Electronic Cigarette Use to Bystanders

Abstract: This works aimed to assess the health risks of e-cigarette use to bystanders. The exhaled breath of 17 volunteers was collected while they were vaping, and the levels of nicotine, propylene glycol, glycerol, formaldehyde, acetaldehyde, acrolein, tobacco-specific nitrosamines (TSNAs), and heavy metals were analyzed. Increased levels of nicotine, propylene glycol, TSNAs and copper were found in the exhaled breath of the volunteers. From these measurements, bystander exposure was estimated for two different scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
3
35
0
5
Order By: Relevance
“…There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211]. Analyses of the health risk of e-cigarette use for bystanders, i.e., passive smoking, indicate that exposure may be associated with irritation of the respiratory tract, systemic effects of nicotine action and increased risk of tumors [212].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 79%
“…There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211]. Analyses of the health risk of e-cigarette use for bystanders, i.e., passive smoking, indicate that exposure may be associated with irritation of the respiratory tract, systemic effects of nicotine action and increased risk of tumors [212].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 79%
“…A modest increase in risk of e-cigarette attributable respiratory diseases such as lung cancer or COPD, or cardiovascular disease, could markedly shift the net evidence base on population effects to support more restrictive regulatory policy on e-cigarettes. Effects of other little studied outcomes of e-cigarette exposure, including in utero exposure to maternal e-cigarette use and secondhand exposure to e-cigarette aerosol in bystanders, could also shift the assessment of respiratory and other population effects 174175. In the US, the assessment of effects may change on the basis of the large increase in use of e-cigarettes in school age young people in 2018, which drove an increase in overall use of any tobacco product, largely erasing recent progress in reducing use in young people 176.…”
Section: Effects On Population Healthmentioning
confidence: 99%
“…The variety of electronic cigarette (e-cigarette) devices available on the market is rapidly increasing. While early models mimic conventional cigarettes (in shape and size), newer models vary in product specifications (shape, size, battery, and tanks) [ 2 , 3 , 4 , 5 , 6 ]. In addition to product specifications, design and flavor characteristics are increasingly elaborate and appealing [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to product specifications, design and flavor characteristics are increasingly elaborate and appealing [ 7 , 8 , 9 ]. Research in recent years has demonstrated that the appeal of e-cigarettes has increased rapidly [ 2 , 3 , 4 , 5 , 6 , 10 ]. The prevalence of e-cigarette use is increasing, mostly among cigarette smokers, but recent research suggests that e-cigarette use is also increasing among non-smokers, and may even be a gateway to smoking [ 2 , 3 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%